New reaction of terminal acetylenes with nitrates in the presence of sulfur trioxide: Heterocyclization into 3-acyl-5-aryl(alkyl)isoxazoles; Russian Journal of Organic Chemistry; Vol. 37, iss. 8 - Rogachev V. O. Victor Olegovich (2001, 2001)
Title screen